2014
DOI: 10.3168/jds.2013-7560
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Evaluation of an ear-attached movement sensor to record cow feeding behavior and activity

Abstract: The ability to monitor dairy cow feeding behavior and activity could improve dairy herd management. A 3-dimensional accelerometer (SensOor; Agis Automatisering BV, Harmelen, the Netherlands) has been developed that can be attached to ear identification tags. Based on the principle that behavior can be identified by ear movements, a proprietary model classifies sensor data as "ruminating," "eating," "resting," or "active." The objective of the study was to evaluate this sensor on accuracy and precision. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 14 publications
(24 reference statements)
6
119
4
5
Order By: Relevance
“…CowManager SensOor data were more weakly correlated with visual observations (r = 0.69, P < 0.01; CCC = 0.59) than the Smartbow system (r = 0.97, P < 0.01; CCC = 0.96). In a previous evaluation of the CowManager SensOor, rumination was strongly correlated with visual observation (r = 0.93, P < 0.01; CCC = 0.93; Bikker et al, 2014). In the current study, rumination was the most subjective for observers to evaluate and showed slight variation among observers (r = 0.89, P < 0.01; interobserver variability).…”
Section: Ruminationmentioning
confidence: 69%
See 4 more Smart Citations
“…CowManager SensOor data were more weakly correlated with visual observations (r = 0.69, P < 0.01; CCC = 0.59) than the Smartbow system (r = 0.97, P < 0.01; CCC = 0.96). In a previous evaluation of the CowManager SensOor, rumination was strongly correlated with visual observation (r = 0.93, P < 0.01; CCC = 0.93; Bikker et al, 2014). In the current study, rumination was the most subjective for observers to evaluate and showed slight variation among observers (r = 0.89, P < 0.01; interobserver variability).…”
Section: Ruminationmentioning
confidence: 69%
“…All power tests were calculated to obtain a power (1 -β) of 0.90 and a type I error probability (α) of 0.05 (2-tailed). Effect size was determined by previous studies (equal to correlation coefficients; Bikker et al, 2014) and was 0.93 for rumination time (Bikker et al, 2014), 0.88 for feeding time (Bikker et al, 2014) and 0.90 for lying time (Ledgerwood et al, 2010). A minimum of 24 cows was needed to meet statistical power requirements and this number was doubled to account for potential instances of missing data (n = 48).…”
Section: This Study Was Conducted At the University Of Kentucky Coldsmentioning
confidence: 99%
See 3 more Smart Citations